Methods of Assessing the Effectiveness of Corporate Governance - K., Jumambayev S.; S., Mukhtarova K. (Farabi Journal of Social Sciences, 2019)
Abstract. The article introduces reader with the key corporate governance ratings, computed by different agencies. It considers the features and methodology of ratings, pursued objectives, as well as the availability of such ratings in Kazakhstan companies. In addition, attention is given for a rating which formed in an academic environment. Based on an analysis of existing ratings and researches which concludes that the scientifically based algorithm of constructing a corporate rating has not yet been created. It is suggested to improve the method of estimation of corporate governance efficiency.